2008
DOI: 10.1121/1.2918545
|View full text |Cite
|
Sign up to set email alerts
|

Comodulation masking release in bottlenose dolphins (Tursiops truncatus)

Abstract: The acoustic environment of the bottlenose dolphin often consists of noise where energy across frequency regions is coherently modulated in time (e.g., ambient noise from snapping shrimp). However, most masking studies with dolphins have employed random Gaussian noise for estimating patterns of masked thresholds. The current study demonstrates a pattern of masking where temporally fluctuating comodulated noise produces lower masked thresholds (up to a 17 dB difference) compared to Gaussian noise of the same sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 61 publications
3
56
0
Order By: Relevance
“…Recent marine mammal masking studies have demonstrated that auditory masking is not limited to noise within a single auditory filter if the noise is non-G (Branstetter and Finneran, 2008;Erbe, 2008;Trickey et al, 2011). These findings are consistent with previous studies with humans (Hall et al, 1984) and a few other animal listeners (Klump et al, 2001;Pressnitzer et al, 2001).…”
Section: Introductionsupporting
confidence: 90%
“…Recent marine mammal masking studies have demonstrated that auditory masking is not limited to noise within a single auditory filter if the noise is non-G (Branstetter and Finneran, 2008;Erbe, 2008;Trickey et al, 2011). These findings are consistent with previous studies with humans (Hall et al, 1984) and a few other animal listeners (Klump et al, 2001;Pressnitzer et al, 2001).…”
Section: Introductionsupporting
confidence: 90%
“…However, this model does not apply well to non-Gaussian broadband noise such as that produced by snapping shrimp (Hall et al, 1984). Recent psychophysical experiments have demonstrated masked thresholds in comodulated noise well below masked thresholds in Gaussian noise of equivalent spectral noise density and bandwidth for synthetic maskers (Branstetter and Finneran, 2008). The only experimental study with actual environmental noise profiles (including snapping shrimp noise) seems to indicate a 6 dB threshold decrease for 10 kHz tones (Trickey et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most studied release-from-masking effects is comodulation masking release (CMR) in which temporally fluctuating maskers have been shown to be less effective in masking than unmodulated Gaussian noise at the same level (e.g., Hall et al, 1984). It has been argued that if this CMR effect exists in fishes, the effective signal-to-noise ratio would be smaller than that measured in the usual masked signal detection experiments conducted on fishes to the extent that typical anthropogenic and other noise may be comodulated (e.g., Branstetter and Finneran, 2008). One component of the experiments reported here was aimed at determining the relative masking effectiveness of unmodulated and comodulated noise in goldfish and if it is reduced, how much masking release takes place.…”
Section: Introductionmentioning
confidence: 87%
“…In general, the predicted masking effectiveness of these more natural maskers would be less than that of white noise maskers if the more natural maskers were effectively comodulated, either due to source characteristics or due to complex transmission pathways. The temporal modulations in environmental noise have generally not been noted, but at least one report has described many of these noises as comodulated (Branstetter and Finneran, 2008) and having a large effect on masking in dolphins (up to 17 dB). Klump and Langemann (1995) have noted, in addition, some of the factors that may cause amplitude fluctuations in the natural terrestrial soundscape.…”
Section: A the Effects Of Anthropogenic Noise On Fishesmentioning
confidence: 99%